A proposed ultra low-noise optical receiver for 1.55 μm applications - Rajamani V.; Chakrabarti P. (My University, 2025)
A high-sensitivity optical receiver based on InP/InGaAs superlattice avalanche photodiode (SL-APD) followed by an InGaAs MESFET transimpedance pre-amplifier has been proposed for operation in 1.55 μm wavelength region. The proposed optical receiver may be realized in the hybrid integrated circuit form. The low excess-noise factor of the SL-APD significantly reduces the value of minimum detectable optical power and improves the sensitivity of the over all receiver. The proposed receiver has been analysed theoretically. The results of computation show that the device has a high transimpedance gain (∼60 dB-ohm) with a bandwidth of 11 GHz for a photodetector capacitance of 110 fF. The sensitivity of the receiver has been found to be (∼-27.3 dBm) at operating bit rate of 15 Gb/s for a bit-error-rate of 10-9. The performance of the receiver can be optimised in respect of transimpedance gain, bandwidth and sensitivity by following guidelines provided in this paper. The proposed photoreceiver outperforms the existing receivers based on p-i-n/FET or conventional APD/FET photoreceivers.